Two or Three Consecutive Days Albendazole Treatment Has Better Efficacy than Single-Dose Albendazole Treatment for Trichuriasis - Dina Evalina Gultom; Muhammad Ali; Ayodhia Pitaloka Pasaribu; Syahril Pasaribu (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Soil-transmitted helminth (STH) infection is endemic in Indonesia. Singledose albendazole is routinely used to control STH infections. Some studies found that repeated-dose of albendazole showed better efficacy. There is no study in Indonesia to compare single-dose and repeated-dose albendazole for against STH infections.METHODS: A randomized, open clinical trial was conducted in July-September 2018 among primary school children. Stool samples were collected before treatment and on day 7, 14, 21, and 28 after treatment then stained using the Kato-Katz method. Group I received three consecutive days, group II received two consecutive days, and Group III received single-dose of albendazole. Cure rate (CR) and egg reduction rate (ERR) were compared using Chi-square tests, and eggs per gram (EPG) was compared using the Kruskal Wallis test (p<0.05).RESULTS: One hundred ninety-five subjects enrolled and divided into 65 subjects in each group. The CR and ERR of trichuriasis after three consecutive days (79.5% and 97.4%) and two consecutive days regimen (70.3% and 91.9%) were higher than single-dose regimen (32.2% and 74.6%) with p<0.001, but not for ascariasis or hookworm infection. The highest efficacy was found in three consecutive days regimen group. Trichuris trichiura EPG was significantly different among the three groups on day 7, 14, 21, and 28 after treatment (p<0.001).CONCLUSION: Three and two consecutive days albendazole have better efficacy than single-dose of albendazole for trichuriasis, but not for ascariasis or hookworm infection. Two consecutive days albendazole is better choice for treating trichuriasis with more adherence and less side effect than three consecutive days regimen.KEYWORDS: soil-transmitted helminth infection, albendazole, single-dose, repeated-dose